Refining drug administration in a murine model of acute infection with Trypanosoma cruzi - Gulin, Julián Ernesto Nicolás (2020)
Background: In animal research, "refinement" refers to modifications of husbandry or experimental procedures to enhance animal well-being and minimize or eliminate pain and distress. Evaluation of drug efficacy in mice models, such as those used to study Trypanosoma cruzi infection, require prolonged drug administration by the oral route (e.g. for 20 consecutive days). However, the orogastric gavage method can lead to significant discomfort, upper digestive or respiratory tract lesions, aspiration pneumonia and even accidental death. The aim of this work was to evaluate the effect of two administration methods (conventional oral gavage vs. a refined method using a disposable tip and automatic pipette) on the efficacy of benznidazole in a murine model of T. cruzi infection.Results: Both administration methods led to a rapid and persistent reduction in parasitaemia. Absence of T. cruzi DNA (evaluated by real-time PCR) in blood, cardiac and skeletal muscle confirmed that treatment efficacy was not influenced by the administration method used.Conclusions: The proposed refined method for long-term oral drug administration may be a suitable strategy for assessing drug efficacy in mice models of Chagas disease and can be applied to similar murine infection models to reduce animal discomfort.